2018
DOI: 10.1016/j.watres.2017.12.077
|View full text |Cite
|
Sign up to set email alerts
|

A tiered approach to assess effects of diclofenac on the brown mussel Perna perna: A contribution to characterize the hazard

Abstract: Pharmaceutical discharges into the aquatic ecosystem are of environmental concern and sewage treatment plants (STPs) have been pointed out as the major source of these compounds to coastal zones, where oceanic disposal of sewage occurs through submarine outfalls. Diclofenac (DCF) is one of the most frequently detected pharmaceuticals in water, but little is known about the effects on marine organisms. In this study, we employed a tiered approach involving the determination of environmental concentrations of DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 80 publications
0
12
0
5
Order By: Relevance
“…Trends in AChE in the digestive gland of Corbicula fluminea (Aguirre-Martínez et al 2018) and R. philippinarum exposed to pharmaceuticals (Aguirre-Martínez et al 2016) indicated variability of this enzyme (depending on the species and pharmaceutical dose). Induction of AChE activity was also observed in the mussels Perna perna (Fontes et al 2018) and Mytilus galloprovincialis (Gonzalez-Rey and Bebianno 2014) exposed to diclofenac. This suggests that the AChE activity influenced by xenobiotics was not particularly high in the study area because the spatial gradient was not markedly evident.…”
Section: Ache Responsesmentioning
confidence: 85%
“…Trends in AChE in the digestive gland of Corbicula fluminea (Aguirre-Martínez et al 2018) and R. philippinarum exposed to pharmaceuticals (Aguirre-Martínez et al 2016) indicated variability of this enzyme (depending on the species and pharmaceutical dose). Induction of AChE activity was also observed in the mussels Perna perna (Fontes et al 2018) and Mytilus galloprovincialis (Gonzalez-Rey and Bebianno 2014) exposed to diclofenac. This suggests that the AChE activity influenced by xenobiotics was not particularly high in the study area because the spatial gradient was not markedly evident.…”
Section: Ache Responsesmentioning
confidence: 85%
“…For example, Dc affected the tissue integrity and immune activity in brown trout at the 5-50 µg/l [2] and was toxic for bivalve mollusk with an LC 50 of 178 µg/l [33]. However, even low concentrations of Dc (20,200,2000 ng/l) decreased the lysosomal membrane stability and COX activity in the brown mussel Perna perna exposed for 48 and 96 h, as well as triggered DNA damage, oxidative stress and changes in antioxidant defenses [34]. Concerning Nf, acute ecotoxicity studies still predominate relatively to the chronic ones [35].…”
Section: Groupmentioning
confidence: 98%
“…The samples were both irradiated under UV environment at 365 nm wavelength by a GY-500 high-pressure mercury lamp for 60 min. The remaining amount of DCFS before and after irradiation was also detected by HPLC-UV (WATERS, Milford, MA, USA) and the degradation efficiency was calculated by Equation (1). The degradation products of DCFS were identified by ultraperformance liquid chromatography coupled with Vion ion mobility separation quadrupole time-of-flight tandem mass spectrometry (UPLC-Vion IMS Q-TOF-MS, ACQUITY I class, Waters, Milford, MA, USA).…”
Section: Degradation Experimentsmentioning
confidence: 99%
“…Diclofenac sodium (DCFS) represents a rising concern due to its ecotoxicological potential and current, sustained release into the aquatic environment. Furthermore, many regions and countries, such as Europe, America, China, and so on, have added DCFS to the priority substances monitoring list of water policy [1][2][3]. Approximately a hundred tons of DCFS are sold annually worldwide, about 15% of which is excreted unchanged by human race and is frequently detected in domestic wastewater [4].…”
Section: Introductionmentioning
confidence: 99%